Evaluation of tomato entries with different combinations of resistance genes to tomato yellow leaf curl disease in Tunisia. Issue 4 (26th May 2016) - Elbaz, Mounira; Hanson, Peter; Fgaier, Salah; Laarif, Asma
Abstract: Tomato yellow leaf curl virus (TYLCV) is one of the most widespread begomoviruses transmitted by the whitefly Bemisia tabaci that cause tomato yellow leaf curl virus diseases (TYLCDs). TYLCD losses can be especially severe in open‐field tomato ( Solanum lycopersicum L.) crops. TYLCV is particularly well known and widespread in the Mediterranean (Med) countries where TYLCD control is mostly based on insecticidal control of B. tabaci populations. Unfortunately, Tunisian B. tabaci populations include Middle East‐Asia Minor I and the Med species that have developed resistance to many classes of insecticides. Therefore, TYLCD‐resistant cultivars are essential for sustainable disease management. Six TYLCD resistance genes ( Ty ) have been introgressed from wild species into cultivated tomato and are available for breeding. Information on the Ty genes or gene combinations is useful for breeding resistant cultivars. To this end, 14 tomato lines carrying different Ty gene combinations and two susceptible tomato entries were evaluated for TYLCD incidence and severity in two field trials during late season in Tunisia. Entries with Ty‐1 / Ty‐3 + Ty‐2 offered the highest levels of resistance in Tunisia.